EVALUASI KINERJA BADAN PERMUSYAWARATAN DESA (BPD) DALAM MENJALANKAN FUNGSI DAN PERANANNYA DI ERA OTONOMI DAERAH (Suatu Studi Di Desa Mosum Distrik Moskona Utara Kabupaten Teluk Bintuni Provinsi Papua Barat ) - OROCOMNA, MUSA; PANGKEY, MASJE; ROMPAS, SONNY (Sam Ratulangi University, 2014)
ABSTRACT : This research purpose to determine the performance evaluation BadanPermusyawaratan Desa(BPD) in performing its functions and its role in the era of regional autonomy,and get an over view about things related to How the achievement of performance in carrying out itsduties and functions in the village Mosum. The method used in this research is descriptive. Were used asinformants in research amount to as many as 10 people.BPD Kampung Mosum absorb the aspirations of the people is done by holding meetings that presents thevarious elements of the villagers; One of the problems that can be solved by the BPD in relation toindigenousaeg is functionis a matter of customary land; Implementation of legislative function byBAPERKA Mor BPD has not been implemented functions properly; oversight function has beenimplemented relatively well by BPD Kampung Mosum, where surveil lanceis done on the implementationof the village budget(APBDes); BPDMosum village, where member ship has reflected the diversity ofsocio-economic status communities that BPD has fulfilled the function of representation. In general, theperformance Consultative Body (BPD) seen from the implementation of the functions has been going well,although not achieving optimal results. It turns out that the legislative function optimally etreceivedattention to the still relatively low level of knowledge and expertise of representatives in formulating adraft Regulation is good village, due to the lowquality of human resources. Recommendations from thisresearch to improve the performance of the necessary involvement of all elements of society, especiallyindigenous stakeholders/heads of tribes in Kampung Mosum.Keywords: Performance Evaluation and Badan Permusyawaratan Desa Function Role, the LocalOtonomy